Knotless barbed suture versus conventional polydioxanone suture material for intraoral surgical incisions - A randomized controlled trial - Himaja Idupulapati; Karthik Ramakrishnan; Cynthia Scott; Vivek Narayanan; Saravanan Chandran; Prashanthi Gurram (Elsevier, 2023)
Purpose: To evaluate and compare the perioperative wound management and healing of intraoral surgical incisions between the conventional and knotless barbed Polydioxanone suture materials. Materials and methods: A Randomized Controlled Trial was conducted with well-constructed inclusion and exclusion criteria. 46 participants were allotted into the control and test groups based on a computer-generated randomization sequence. The materials used were 3-0 Stratafix™ knotless barbed PDS suture and conventional 3-0 Ethicon PDSTMII suture materials. Parameters assessed included intraoperative time taken for closure and assessment with Early Wound Healing Score (EHS) on postoperative day 1 and Landry, Turnbull, and Howley (LTH) Healing index on postoperative days 3 and 7. Statistical analyses were done using the Chi-square test and student's t-test with a p-value less than 0.05 indicating statistical significance. Results: 32 patients had surgical intervention for maxillofacial fracture management and 14 patient for orthognathic osteotomies. Surgical sites (n = 60) included maxillary and mandibular vestibules. Intraoperative closure time was better in the test group with statistical significance (p-value = 0.0472). The healing scores on the 3rd and 7th postoperative days were compared between the control and test groups exhibiting statistical significance favouring the test group. The p-values were 0.0479 and 0.0393 respectively. Conclusion: To conclude, our study concurred with the existing literature in terms of reduced operating time, and better wound healing observed with the knotless barbed suture. Along with statistical significance, all the variables exhibited clinical relevance and better wound management in the test group.